2010
DOI: 10.1002/humu.21387
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting loss of heterozygosity (LOH) in neurofibromatosis type 1-associated neurofibromas: Importance of copy neutral LOH

Abstract: Dermal neurofibromas (dNFs) are benign tumors of the peripheral nervous system typically associated with Neurofibromatosis type 1 (NF1) patients. Genes controlling the integrity of the DNA are likely to influence the number of neurofibromas developed because dNFs are caused by somatic mutational inactivation of the NF1 gene, frequently evidenced by loss of heterozygosity (LOH). We performed a comprehensive analysis of the prevalence and mechanisms of LOH in dNFs. Our study included 518 dNFs from 113 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 43 publications
2
57
0
1
Order By: Relevance
“…The identification of NF1-associated LOH (probably associated with mitotic recombination) in 24 tumours is consistent with the results reported in a recent study of neurofibromas that assessed NF1-associated LOH in this type of tumour. 47 In our study, MLPA analysis succeeded in identifying only a single intragenic deletion in one neurofibroma, indicating that mitotic recombination was the likely mechanism for LOH in the remaining 24 neurofibromas. Our previous studies found significantly higher levels (approximately 70 and 90%, respectively) of NF1-associated LOH in both PNFs and MPNSTs, 17,18 an indication that NF1-LOH may be less prominent in benign neurofibromas than in PNFs and malignant tumours.…”
Section: Discussionmentioning
confidence: 54%
“…The identification of NF1-associated LOH (probably associated with mitotic recombination) in 24 tumours is consistent with the results reported in a recent study of neurofibromas that assessed NF1-associated LOH in this type of tumour. 47 In our study, MLPA analysis succeeded in identifying only a single intragenic deletion in one neurofibroma, indicating that mitotic recombination was the likely mechanism for LOH in the remaining 24 neurofibromas. Our previous studies found significantly higher levels (approximately 70 and 90%, respectively) of NF1-associated LOH in both PNFs and MPNSTs, 17,18 an indication that NF1-LOH may be less prominent in benign neurofibromas than in PNFs and malignant tumours.…”
Section: Discussionmentioning
confidence: 54%
“…LOH of 22q in tumours from patients with germline SMARCB1 mutations does not seem to be mediated by mitotic recombination, a mechanism frequently causing LOH of other tumour suppressor genes (Makishima and Maciejewski 2011; Garcia-Linares et al 2011; Stewart et al 2012). In eight tumours from patients with germline SMARCB1 mutations, LOH of 22q was found to be caused exclusively by whole chromosome loss or large deletions within 22q, but not by mitotic recombination (Hadfield et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with Knudson's two-hit hypothesis, biallelic NF1 inactivation is required for tumorogenesis [12]. While the "first hit" is a germ-line mutation, the "second hit" is a somatic mutation which might occur in utero or later leading to inactivation of NF1 [13,14]. Recent reports shows that even haploinsufficiency also have functional implications [15].…”
Section: Discussionmentioning
confidence: 73%